A COMSOL-PHREEQC interface for modeling the multi-species transport of saturated cement-based materials. (30th October 2018) - Guo, Bingbing; Hong, Yi; Qiao, Guofu; Ou, Jinping
Highlights: A COMSOL-PHREEQC interface is developed to model the multi-species transport. The interface is based on the physiochemical essential processes of the transport. The interface is verified by the two published experiments. Abstract: A COMSOL-PHREEQC interface based on MATLAB language is developed to simulate a multi-dimensional and multi-species ionic transport for cement-based materials. This interface couples the physical and chemical interactions between pore solution and cement hydrates (PHREEQC) into the Nernst-Planck equations (COMSOL) using a sequential non-iterative approach (SNIA). Based on the thermodynamic insight, the phase-equilibrium model and the surface complexation model are used to express the physical and chemical interactions. In addition, the influence of the variation of the porosity on the ionic transport is considered. Moreover, two reported experiments are taken as an example to illustrate the application of the interface and to verify its accuracy. The results indicate that the developed interface can accurately predict the transport of chloride in cement-based materials.